The molecular ecology and evolution of puma letivirus in bobcats and mountain lions in North America - Lee, Justin S., author; VandeWoude, Sue, advisor; Crooks, Kevin R., advisor; Funk, W. Chris, committee member; Troyer, Jennifer L., committee member (Colorado State University. Libraries, 2013)
Host-pathogen dynamics are influenced by ecological and evolutionary processes at all levels of biological organization. Within individuals, viruses that cause chronic infection must either avoid or escape the pressures of the host immune system. Furthermore, viruses adapted to one host environment may have low fitness when transmitted to different individuals, populations, and species. At the landscape level, the movement and distribution of directly transmitted obligate pathogens are inextricably associated with their hosts. We used molecular analyses to investigate the ecology and evolution of feline immunodeficiency virus (FIV) in bobcats and mountain lions within individuals, among populations, and between species of hosts. In Chapter One we investigated the effects of urban development on the movement of bobcats and feline immunodeficiency virus (FIV) among a fragmented landscape in southern California. Our results demonstrate that bobcat movement and gene flow are restricted across a major freeway that bisects the study area, resulting in two genetically and physically distinct subpopulations connected by a low level of migration. However, the FIV population is not similarly structured, suggesting that movements and contacts sufficient for disease transmission continue despite the low level of host migration observed. Chapter Two investigates the causes and effects of FIV evolution among bobcats and mountain lions across North America. Our results illustrate a dynamic host-pathogen relationship characterized by host-immune pressures and a rapidly evolving virus with a highly plastic genome. Finally, in Chapter Three we describe a pilot project aimed at improving the efficiency with which pathogen genetic data can be collected by combining the use of two modern technologies - targeted genome capture and next-generation sequencing. The results suggest this is a promising approach to detecting and sequencing multiple pathogens from biological samples. Collectively, the work described in this dissertation combines new and existing methodologies to generate, analyze, and interpret molecular data to answer complex questions about the ecological and evolutionary determinants of host-pathogen dynamics.
Keywords: disease ecology; feline immunodeficiency virus; puma concolor; puma lentivirus; viral evolution; Lynx rufus